Formulation of new sourdough bread prototypes fortified with non-compliant chickpea and pea residues - Cutroneo, Sara; Petrusan, Janos-Istvan; Stolzenberger, Reiner; Zurlini, Chiara; Tedeschi, Tullia (Frontiers in Nutrition, 2024)
Purpose Nowadays, the promotion of a circular economy is fundamental to reduce food losses and waste. In this context, the possibility of using food supply chains non-compliant residues emerges. Much interest has been directed toward legume residues, in general and, in particular, to the possibility of combining different plant-matrices to improve nutritional profile, providing high-quality products. Methods Five different formulations of breads, with a combination of seeds and cereals, were fortified with chickpea and pea protein concentrates. Samples were analyzed and compared with their relative control recipe to determine differences in composition, actual protein quality and integrity, and protein digestibility (performed with the INFOGEST method). Results Samples showed a clear improvement in the nutritional profile with higher values of proteins, from averagely 12.9 (control breads) to 29.6% (fortified breads) (17.7–24.7 g/100 g of dry matter respectively), and an improvement in amino acidic profile, with a better balancing of essential amino acids (lysine and sulfur amino acid contents), without affecting protein integrity. Regarding in vitro gastro-intestinal digestibility, sample C (19% chickpea proteins) showed the best results, having a comparable protein digestibility to its control bread—48.8 ± 1.1% versus 51.7 ± 2.3%, respectively. Conclusion The results showed how the fortification with chickpea and/or pea protein concentrate improved the nutritional profile of bread. These prototypes seem to be a valid strategy to also increase the introduction of high biological value proteins. Furthermore, the not-expected lower digestibility suggested the possible presence of residual anti-nutritional factors in the protein concentrates interfering with protein digestibility. Therefore, it seems of fundamental importance to further investigate these aspects.